Fractionated stereotactic radiotherapy in people with drug-resistant focal epilepsy: first-in-human experience with a healthy tissue-preserving dose-fractionation concept - Cas Stefaan Dejonckheere; Attila Rácz; Gustavo Renato Sarria; Julian Philipp Layer; Julian Philipp Layer; Younèss Nour; Lara Caglayan; Molina Grimmer; Victoria Volkenborn; Fabian Kugel; Thomas Müdder; Tobias Baumgartner; et al. (Frontiers in Neurology)
ObjectiveStereotactic radiosurgery (SRS) emerges as a non-surgical treatment option for drug-resistant non-neoplastic focal epilepsy. Previous studies have reported that in about 20% of patients treated with radiotherapy, however, subsequent salvage surgery is required, among other because of symptomatic radiation necrosis (RN). We propose a novel and radiobiologically substantiated dose-fractionation regimen which minimizes the RN risk while aiming to preserve efficacy and report our first-in-human experience.MethodsFrom February 2021 to April 2024, three patients (aged 42, 45, and 47 years) with different underlying etiologies were treated, including a post-hemorrhagic lesion, Rasmussen encephalitis, and focal cortical dysplasia. We applied linac-based frameless fractionated stereotactic radiotherapy (fSRT) to a total dose of 50 Gy in 10 fractions over 2 weeks. Each epileptogenic zone was defined by a multidisciplinary team, including a radiation oncologist, epileptologist, neurosurgeon, and neuroradiologist.ResultsThe irradiated volumes were 10.3, 11.3, and 16.5 cm3. After a follow-up of 12, 29, and 36 months, all three patients experienced an improvement in both seizure frequency and severity (two already during or shortly after fSRT). One patient achieved complete seizure freedom. All patients reported improvements in quality of life and regained independence or displayed functional recovery. Tolerability was excellent, with radiation-induced side effects being mild (grade 1 only) and transient. RN was not observed. One patient died 29 months after radiotherapy most likely from a ruptured aneurysm of a vertebral artery, unrelated to the treatment.SignificanceFrameless fSRT of 50 Gy in 10 fractions was feasible and might be safe and effective in selected patients with drug-resistant non-neoplastic focal epilepsy and large suspected epileptogenic zones. A prospective single-arm evaluation with structured long-term follow-up including assessment of patient-reported outcome measures is currently being conducted.